Transformative Governance: Utilizing Social Media Dynamics to Improve Public Service Implementation in the Digital Age in Indonesia - Syaftiani, Mella; Nurmandi, Achmad; Misran, Misran; Younus, Muhammad (Nyimak: Journal of Communication, 2024)
The widespread use of social media has fundamentally transformed how people communicate, collaborate, and interact, leading to significant shifts in social structure and contemporary cultural order. This study aims to analyze the role of social media in revolutionizing public service implementation in the digital era. The research uses a qualitative approach, utilizing Google Collab and Nvivo as analytical tools. Key findings reveal that internet usage is dominated by adolescents and adults, which accelerates the adoption of public services through social media, primarily due to the high level of technological literacy among users. The results of this study contribute to the literature by highlighting the role of social media as an effective tool to overcome the limitations of conventional communication in public services. The practical implications of this study indicate the potential for improving public service standards at the international level through the optimization of social media to reach the community more broadly and efficiently.Keywords: social media, e-government, e-governance, innovation division, web 2.0AbstrakPenggunaan media sosial yang luas telah secara mendasar mengubah cara orang berkomunikasi, berkolaborasi, dan berinteraksi, serta menyebabkan pergeseran signifikan dalam struktur sosial dan tatanan budaya kontemporer. Penelitian ini bertujuan untuk menganalisis peran media sosial dalam merevolusi implementasi pelayanan publik di era digital. Metode yang digunakan adalah pendekatan kualitatif dengan memanfaatkan alat analisis Google Collab dan Nvivo. Temuan utama menunjukkan bahwa penggunaan internet didominasi oleh remaja dan orang dewasa, yang mempercepat adopsi layanan publik melalui media sosial, terutama karena tingginya tingkat literasi teknologi di kalangan pengguna. Hasil penelitian ini berkontribusi pada literatur dengan menekankan peran media sosial sebagai alat efektif untuk mengatasi keterbatasan komunikasi konvensional dalam pelayanan publik. Implikasi praktis dari penelitian ini menunjukkan potensi peningkatan standar pelayanan publik di tingkat internasional melalui optimalisasi media sosial untuk menjangkau masyarakat secara lebih luas dan efisien.Kata Kunci: media sosial, e-government, e-governance, divisi inovasi, web 2.0